ANALISIS PENGARUH TUNJANGAN KINERJA DAN KOMPENSASI TERHADAP MOTIVASI KERJA PEGAWAI - Absor, Ulul; ', Amsirun; Rahayu, Sri (Jurnal Strategik, 2025)
This study, entitled "The Effect of Performance Allowances and Compensation on Employee Work Motivation," was conducted at State Islamic Senior High School (MAN) 1, Tegal Regency. Multiple linear regression analysis, t-test, F-test, and coefficient of determination were used.The results of the research that has been conducted are that partially performance allowances have an influence on work motivation. This is proven by the results of the t-test using a 95 percent confidence level and degrees of freedom N-k (21-2) obtained a t-table of 1.729 and the results of calculations in SPSS show that the performance allowance variable (X1) = 1.984 which means that t-count > t-table. This shows that Ho is rejected or the performance allowance variable has a significant effect on work motivation, and compensation (X2) = 0.019 which means that t-count < t-table. This shows that Ho is accepted or compensation does not have a significant effect on work motivation.Simultaneously, the performance allowance variable and compensation variable together or simultaneously have an influence on work motivation, this is proven by the F Test conducted using a 95 percent confidence level (α = 0.05) and df = n – k – 1 obtained Ftable of 3.55. While the calculation results show 17.488. This shows that F count > F table which means the Ho hypothesis is rejected which means that together the independent variables performance allowance (X1) and compensation (X2) have an influence on employee work motivation. Keywords: Performance Allowance, Compensation and Work Motivation